Effects on the compressive strength of cement-stabilized rammed earth blocks with varied content of buffelgrass-based fibers in wet-dry conditions - Pederson, Federico; Florendo, Reuel; Khawaja, Saleh Ali; Dimond, Kirk; Kim, Hee-Jeong (Frontiers in Built Environment, 2024)
Stabilized rammed earth blocks have been an alternative building material around the world due to their cost efficiency, low embodied energy, and environmental footprints. However, the lower compressive strength and resistance to wearing limits their use in comparison to higher-cost alternatives. The integration of fibers in rammed earth blocks has been a promising technique for enhancing their properties. In this research, the viability of buffelgrass as a reinforcing fiber in stabilized earth blocks was determined. The buffelgrass was incorporated into the mix up to 5% by weight for samples with the increment of 1% for each mix and the durability was determined under wet and dry conditions. In addition, the influence of the buffelgrass on the compressive strength was observed and the optimum content was determined. The morphological characteristics were observed using SEM imaging of the rammed earth and fiber interaction at a fracture surface. The results showed the inclusion of buffelgrass helps the wear resistance of the earth blocks when exposed to wet-dry conditions as well as slightly improving the compressive strength of the material after dry and wet curing.